2021
DOI: 10.15421/022175
|View full text |Cite
|
Sign up to set email alerts
|

Course correction of adjuvant arthritis with cryopreserved multipotent mesenchymal stromal cells

Abstract: Rheumatoid arthritis is an inflammatory autoimmune disease that occurs as a result of impaired immune tolerance, leading to an aberrant immune response to autologous antigens. Multipotent mesenchymal stromal cells (MMSCs) and the biologically active substances they produce can promote the activation of regenerative processes in the organism not only by direct cell differentiation, but also due to their inherent trophic and immunosuppressive potentials. The aim of the study was to experimentally evaluate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In our previous studies, we found that CrMMSCs could affect the reparative and regenerative processes in animals with both acute and chronic phases of inflammation [19,20]. Local and generalized administration of CrMMSCs from adipose and cartilage tissues led to correction of the course of experimental AA in rats.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous studies, we found that CrMMSCs could affect the reparative and regenerative processes in animals with both acute and chronic phases of inflammation [19,20]. Local and generalized administration of CrMMSCs from adipose and cartilage tissues led to correction of the course of experimental AA in rats.…”
Section: Discussionmentioning
confidence: 94%